El cine en el horizonte transmedia: entre la franquicia y el dispositivo de narración - Cappello Flores, Giancarlo (2016)
The text proposes some precisions around the so-called transmedia cinema in the frame of multiplatform narratives. For this reason, the creative role of audiences and their repercussion in the development of stories, as well as the logic behind the principles of multiplicity and expansion, are especially disaggregated. Finally, in the light of recent productions, the author describes some practices and uses of technology that would bring cinema to a transmedia experience.